Crystallization and preliminary X-ray diffraction analysis of the Nif3-family protein MJ0927 from Methanocaldococcus jannaschii - Kuan, Shu-Min (International Union of Crystallography, 2012)

(untitled)
MJ0927 is a member of the Nif3 family and is widely distributed across living organisms. Although several crystal structures of Nif3 proteins have been reported, structural information on archaeal Nif3 is still limited. To understand the structural differences between bacterial and archaeal Nif3 proteins, MJ0927 from Methanocaldococcus jannaschii was purified and crystallized using the sitting-drop vapour-diffusion method. The crystals diffracted to a resolution of 2.47 Å and belonged to the orthorhombic space group C222, with unit-cell parameters a = 81.21, b = 172.94, c = 147.42 Å. Determination of this structure may provide insights into the function of MJ0927.